PENGARUH KOMBINASI PUPUK KANDANG SAPI DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SORGUM: Kata kunci: Kata kunci: pupuk kandang sapi, NPK, sorgum, hasil. - Novita Eka Kumalasari; Priyono Priyono; Saiful Bahri (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2022)
The study was conducted to determine the response between cow manure and NPK fertilizer which affects the growth and yield of sorghum plants. The activity was carried out in the experimental garden of the Faculty of Agriculture, Slamet Riyadi University, Surakarta on November 18, 2021 to March 16, 2022, with a 2 factor completely randomized design (CRD), then replicated 3 times. The first factor used cow manure (S) with 4 levels, namely (S0) Control, (S1) dose of 120 grams/polybag, (S2) dose of 240 grams/polybag, (S3) dose of 360 grams/polybag. The second factor is NPK fertilizer (N), (N0) Control, (N1) at a dose of 3 grams/polybag, (N2) at a dose of 6 grams/polybag, (N3) at a dose of 9 grams/polybag. The conclusion of this study is that the concentration of cow manure treatment at 120 grams/polybag and NPK fertilizer dose of 6 grams/polybag gave the best results at plant height of 260.07 cm, number of leaves 8.51 sheets, stem circumference 9.43 cm, seed weight per panicle. 169.67 grams, the number of seeds per panicle 1062.65 seeds, dry stover weight 1567.23 grams, dry stover weight 1344.66 grams.